Analisis Pengaruh Financial Forecasting Terhadap Efisiensi Pengelolaan Keuangan Bagi UMKM. - Ari Nugroho Cahyono; Nia Rifanda Putri (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
This study aims to analyze the role of financial forecasting as a basis for financial planning, control, and decision-making, as well as its influence on the efficiency of financial management in MSMEs. This research employs a qualitative research design with a case study approach. Data were collected through in-depth interviews and focus group discussions (FGDs) involving key informants directly engaged in financial and operational management. Data analysis was conducted using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The findings indicate that MSME financial management is still predominantly based on experience and manual record-keeping, resulting in the absence of systematic financial forecasting practices. However, financial forecasting is perceived to enhance the accuracy of financial information, improve operational efficiency, and support higher-quality financial decision-making when supported by adequate financial records. This study concludes that financial forecasting represents a strategic managerial accounting instrument for improving the efficiency of MSME financial management, with its effectiveness largely dependent on the quality of financial records and the accounting competence of business actors. Keywords: financial, forecasting, financial management efficiency, MSMEs.